Home health utilization association with discharge to community for people with dementia. Issue 1 (26th July 2022) - Knox, Sara; Downer, Brian; Haas, Allen; Ottenbacher, Kenneth J.
Abstract: Introduction: The objective of this study was to identify home health utilization factors associated with successful discharge to community after home health care for patients with and without Alzheimer's disease and related dementias (ADRD). Methods: This was a retrospective study of 100% national Medicare home health data files (2016 to 2017). Multilevel logistic regression was used to study the relationship of home health utilization with a modified definition of successful discharge to community (M‐SDC) after home health (no readmission or discharge within 30 days). Significant interactions were identified using backward selection. The associations between domains were examined in a model stratified by ADRD, with and without controlling for mobility, self‐care, and caregiver assistance. Results: The cohort consisted of 535, 691 patients, 18.0% with ADRD. The overall M‐SDC rate was 92.1%. The likelihood of M‐SDC was increased when physical therapy services were provided, episodes of care were longer than 15 days, and the total number of therapy visits was greater than 10. The likelihood of M‐SDC decreased when speech therapy, nursing, and home health aide services were provided and when patients were discharged early. When controlling for mobility, self‐care, and caregiver support, length of home health episode was the only characteristic that showed a significant interaction with ADRD. Discussion: The results of this study indicate that the provision of physical therapy services and moderate lengths of care and volume of visits are associated with increased likelihood of M‐SDC. A decreased likelihood of M‐SDC when speech therapy, nursing, and home health aide services are delivered may be a proxy indicator of patient acuity and disease severity and needs to be further investigated. An important next step in understanding home health access and outcomes for people with ADRD is to examine the impact of the Patient‐Driven Groupings Model on home health utilization characteristics, especially length of episodes. Highlights: Most people remain in the community after discharge from home health. Likelihood of modified successful discharge to community (M‐SDC) increased with physical therapy, longer episodes, and more than 10 visits. Likelihood of M‐SDC decreased with speech therapy, skilled nursing, home health aide visits, and early discharge. Longer home health episodes increased likelihood of M‐SDC for people with Alzheimer's disease and related dementias.